A Study on Emerging Retail Banking Activities in context of Revenue Generation for Indian Banking Industry: The Impact of Emerging Retail Banking Activities on Revenue Generation in the Indian Banking Industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Retail Banks are considered as a backbone to the financial system and it plays a crucial role in the economic development of a nation. They also act as various intermediaries who are channelizing funds from surplus units to actually deficit various units to the fully utilization of thefunds. An efficient banking system of nations plays a significant role in positive externalitieswhich also increases the efficiency of the economic transaction which is in general. There is amajor shift in the banking system of the policy atmosphere immediately after the introduction of the financial sector reform since 1992 these reforms created an impact on the working of the commercialbanks. As it is termed as one of the major objectives of financial sector which reforms and also tries to improve theefficiency of banking system in the India economy. Financial System of any country also consists of financial markets, financial intermediation and even financial instruments or financial products in generating revenue in retail banking. The present research paper focuses on emerging retail banking activities in context of revenue generation. It also focuses on the retail banking scenario of the world.